Sosialisasi Pemanfaatan Ketela Sebagai Bahan Dasar Nugget untuk Ibu Rumah Tangga Dusun Jebug Kabupaten Banjarnegara - Jovan Wijaya; Muhammad Reza Andhika Damascena; Charina Yovika Firstianing Tyas; Vincentia Ananda Arum P (Universitas Katolik Soegijapranata, 2019)
Cassava or Manihot esculenta is one of agricultural potential in Dusun Jebug. Usually, harvested cassava is being sold directly to the market or consumed themselves by steaming it first. This phenomenon shows that despite cassava’s high production rate, Dusun Jebug hasn’t process it to its maximum potential resulting the low economic value in said cassava. Which is why innovation in cassava based food product is needed, one of which is making it into nugget. The steps to make cassava nuggets are: (1) steam the cassavas until it become tender, (2) crush the steamed cassava until the surface become smooth, (3) Mix it with butter, water and flour, (4) Stir until the mixture is formed, (5) shape the dough and fill the filler, (6) coat it with flour mixture, (7) mix with bread crumps and, (8) Fry it. Cassava nugget can increase the economic value of cassava and increase the cassava development in Dusun Jebug.